SOSIALISASI DAN PELATIHAN PENGOLAHAN LIMBAH KOTORAN SAPI MENJADI PUPUK ORGANIK DI DESA GEMAWANG, NGADIROJO, WONOGIRI - Widijanto, Hery; Putri, Adelia; Raharja, Chandra Khahendra Edwin; Vitasari, Erlia Nur; Nur, Farid Ramzi; Ari Wibisono, Nyekti (Inisiasi, 2025)
Gemawang Village, located in Ngadirojo District, Wonogiri Regency, has a majority of the population working in the agriculture and livestock sectors. Most of the livestock in this village are cows. One of the problems in this village is that cow dung has not been handled properly, so it can pollute the environment and cause an unpleasant odor. Farmers still use chemical fertilizers that can reduce soil fertility, damage the balance of the soil ecosystem, and even have an impact on reducing agricultural yields. The purpose of this activity is to provide training to farmers in Gemawang Village on how to process cow dung into environmentally friendly and efficient organic fertilizer. The methods used include problem identification, outreach to the community, and practical training for farmers. Training for farmers includes steps in fermenting cow dung with additional materials such as EM4 and rice husks to produce quality organic fertilizer. The results of this program show an increase in farmers' skills in processing cow dung into fertilizer. By utilizing organic fertilizer, farmers can reduce environmental pollution, improve the quality of agricultural products, and encourage more environmentally friendly and sustainable agricultural practices in Gemawang Village. The use of organic fertilizer is also expected to increase the income of farmers by reducing the cost of purchasing chemical fertilizers, as well as creating a healthier, more productive, and sustainable agricultural ecosystem. The conclusion of this study is that the use of cow dung as organic fertilizer can support more sustainable and environmentally friendly agriculture and help improve the quality of agricultural products in Gemawang Village.